Alpha-Angelica lactone catalyzed oxidation of benzylic sp(3) C-H bonds of isochromans and phthalans - Thatikonda, Thanusha; Deepake, Siddharth K.; Kumar, Pawan; Das, Utpal (Organic & Biomolecular Chemistry, 2020)
A metal-free organocatalytic system has been developed for highly efficient benzylic C-H oxygenations of cyclic ethers using oxygen as an oxidant. This oxidation reaction utilizes alpha-angelica lactone as a low cost/low molecular weight catalyst. The optimized reaction conditions allow the synthesis of valued isocoumarins and phthalides from readily available precursors in good yields. Mechanistic studies indicate that the reaction pathway likely involves a radical process via a peroxide intermediate.